Analisis Penyebab Penurunan Temperatur Pada Sistem Permesinan di Kapal - Wahyu Ari Putranto; Shendi May Rudin; Yulius Oscar; Khaeroman Khaeroman; Noviarianto Noviarianto; Ngatmin Ngatmin (PPPM Polimarin, 2026)
Marine generators play a crucial role in supplying electrical power for overall ship operations. This study aims to investigate the factors causing the temperature drop in the Marine Fuel Oil (MFO) system of the generator on MV. Radiant Reb. The temperature decrease (to 98ºC-100ºC) leads to increased fuel viscosity, flow resistance, and a decline in both combustion efficiency and diesel generator performance. By applying a descriptive-qualitative case study approach involving direct observation, interviews, and documentation, this research identified four primary causes. These factors include: reduced heater performance due to scaling and leaks, a suboptimal steam trap causing condensate buildup, damaged thermal insulation (lagging) accelerating heat loss, and wear on the circulation pump disrupting fuel flow. Corrective measures were implemented through routine maintenance and thorough inspections of these vital components. In conclusion, preventive maintenance and early detection are crucial for maintaining the fuel temperature within the ideal range (108ºC-118ºC) to preserve the operational efficiency and reliability of the marine generator.